DWUGŁOS W SPRAWIE POJĘCIA ŚWIADCZENIA W POLSKIM PRAWIE CYWILNYM – CHARAKTER PRAWNY SPEŁNIENIA ŚWIADCZENIA - Antas, Marek; Łukasiewicz, Jakub M. (Zeszyty Prawnicze, 2016)
A dialogue Concerning the Notion of Service in Polish Civil Law: the Legal Nature of Accomplishment of Service Summary This paper is the second part of an article constructed on the basis of a dialogue between J.M. Łukasiewicz and M. Antas. The authors attempt to answer the question whether a service is a factual action or a legal action. Next they present the problem of services against a historical background i.e. in Roman Law, in the German and Roman system, and in Polish law. Finally they discuss the question of the causality of legal actions.